The Relationship between Entrepreneurship and Corporate Governance The Case of Romanian listed Companies - Nadia Albu; Ruxandra Adriana Mateescu (Amfiteatru Economic Journal, 2015)
This paper offers an investigation at a micro-level of entrepreneurship in the business environment. More precisely, we conduct an empirical study of the relationship between corporate entrepreneurship and corporate governance in the case of the Romanian non-financial listed companies. We use publicly-available information (financial statements, annual reports) and we mobilize a framework derived from the agency and signalling theories to interpret our findings from the statistical analysis based on correlations. Our results suggest that there are differences between industries and between the companies included or not in the new BET-TR index in terms of corporate entrepreneurship and corporate governance practices and disclosures. Agency theory partly explains our findings. Specifically, some corporate governance mechanisms, i.e. board independence and institutional ownership, are associated in our sample with corporate entrepreneurship. We thus document that corporate governance as a controlling and management technique fosters corporate entrepreneurship in Romanian companies. Signalling theory assumptions are generally not verified for the companies in our study. There are only a few associations between high values of corporate entrepreneurship and corporate entrepreneurship disclosures, and even fewer between corporate governance practices and corporate governance disclosures.
Keywords: M14; L26; G34; 330; corporate entrepreneurship; corporate governance; Romania; agency theory; signalling theory